REDEFINING TEACHER COMPETENCIES IN THE AGE OF GENERATIVE AI: A GLOBAL PERSPECTIVE ON PEDAGOGICAL TRANSFORMATION - Asnawan Asnawan; Andi Nuzul Hikmah Buana; L.Virginayoga Hignasari (International Journal of Teaching and Learning, 2025)
The global educational transformation triggered by the emergence of generative artificial intelligence has demanded a fundamental redefinition of teacher competencies. This study aims to re-examine the pedagogical competencies needed by teachers in facing the era of generative AI, using a literature review approach to the latest international scientific sources. This study explores how artificial intelligence is changing the traditional role of teachers, highlighting the need for new skills such as advanced digital literacy, ethical use of technology, collaborative creativity, and adaptive abilities to AI-based learning ecosystems. The findings of this study indicate that future teacher competencies must not only include technological skills, but also a deep understanding of the critical, ethical, and contextual integration of AI into teaching practices. This study also identifies global challenges such as the digital divide, lack of continuous professional training, and the need for educational policies that are responsive to technological developments. Thus, the redefinition of teacher competencies is not just a technical demand, but a strategic process in creating a fair, inclusive, and sustainable pedagogical transformation amidst digital disruption.